2022
DOI: 10.3390/su14010447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Granular Activated Carbon on Anaerobic Process and Microbial Community Structure during Mesophilic and Thermophilic Anaerobic Digestion of Chicken Manure

Abstract: In this work, the impact of granular activated carbon (GAC) on the mesophilic and thermophilic anaerobic digestion of chicken manure and the structure of microbial communities was investigated. These results demonstrated that GAC supplementation effectively enhanced the consumption of produced organic acids in the mesophilic and thermophilic batch tests, accompanied by faster biomethane production in the presence of GAC than from reactors without GAC. However, since the free ammonia level was 3–6 times higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 66 publications
4
12
0
Order By: Relevance
“…Our results are consistent with the positive effects of GAC, biochar, and magnetite on CH 4 production during the anaerobic digestion of different other substrates as reported in several other works [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 ]. Yang et al [ 16 ] indicated that the addition of GAC to biogas reactors (33.3 g L −1 ) enhanced the CH 4 production by 17.4% over the course of anaerobic sludge digestion.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are consistent with the positive effects of GAC, biochar, and magnetite on CH 4 production during the anaerobic digestion of different other substrates as reported in several other works [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 ]. Yang et al [ 16 ] indicated that the addition of GAC to biogas reactors (33.3 g L −1 ) enhanced the CH 4 production by 17.4% over the course of anaerobic sludge digestion.…”
Section: Resultssupporting
confidence: 93%
“…Total solids, volatile solids, pH, volatile organic acids (VOA), and total ammonia nitrogen (TAN) were measured following standard methods as explained in detail previously [ 20 , 21 ]. Samples for these analyses were periodically collected, and the analyses were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations